Building Governance Based on the Experience Acquired by Municipal Youth Councils in the Colombian Central-Eastern Region: A Case Study - Diego Edgardo Rojas-Escobar (Universidad Nacional, Costa Rica, 2015)
This research presents the findings of a case study conducted in the central-eastern region of Colombia. Based on the existing regulations and those not yet in force, an approach to the experience of the Youth Municipal Councils of Tunja and Paipa was made, which allowed us to identify engagement scenarios, processes, and dynamics that have contributed to the governance building process. The research was conducted considering legal and theoretical aspects, as well as the dynamics that have characterized the Municipal Youth Councils (CMJ, in Spanish) in department and municipal administrations since 2006 until 2013. Subsequently, it will allow us to analyze the new youth statute. A source file analysis is applied, among other research techniques.